2016
DOI: 10.4172/2376-127x.1000292
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Exposure to Antibiotics in Children Less Than 6 Years of Age: A Survey in a Portuguese Metropolitan Area

Abstract: Background: The contact with antibiotics at an early age may lead to a number of nefarious consequences. Nevertheless, the amount of literature available on the usage of antibiotics in children is scarce. Taking into account the increasing emergence of resistant bacterial strains, it is imperative to study and make society aware of the excessive exposure of children to antibiotics. The purpose of this study was to evaluate the incidence of antibiotic therapy in children under the age of six, in the metropolita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies done in Nigeria con-firmed that the exposure to antibiotics in children under 5 years of age is exceptionally high 35 . Studies from Portugal, Jordan, and Ethiopia also reported very high antibiotics exposure in children under 5 and fewer than 6 years of age [36][37][38] . Furthermore, this study revealed that increasing the number of medicines per encounter also increased the risk of receiving an antibiotic prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in Nigeria con-firmed that the exposure to antibiotics in children under 5 years of age is exceptionally high 35 . Studies from Portugal, Jordan, and Ethiopia also reported very high antibiotics exposure in children under 5 and fewer than 6 years of age [36][37][38] . Furthermore, this study revealed that increasing the number of medicines per encounter also increased the risk of receiving an antibiotic prescription.…”
Section: Discussionmentioning
confidence: 99%